1986
DOI: 10.7863/jum.1986.5.7.361
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal sonographic findings in trisomy 18.

Abstract: The clinical and sonographic findings of trisomy 18 are varied. Fifteen cases of trisomy 18 were retrospectively reviewed with attention to demonstrable antenatal sonographic features. Certain combinations of findings, particularly in the third trimester, seem highly suggestive of this diagnosis. A late antepartum diagnosis is warranted because of the poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 3 publications
(3 reference statements)
0
22
0
Order By: Relevance
“…Previously published reports detailing the sonographic findings with trisomy 18 show that, although choroid plexus cysts are seen frequently, most are present with other sonographic findings. [5][6][7][8][9][10][11][12][13] In the 223 fetuses from these combined series that had second-trimester sonograms, isolated choroid plexus cysts were not a common finding (6.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published reports detailing the sonographic findings with trisomy 18 show that, although choroid plexus cysts are seen frequently, most are present with other sonographic findings. [5][6][7][8][9][10][11][12][13] In the 223 fetuses from these combined series that had second-trimester sonograms, isolated choroid plexus cysts were not a common finding (6.7%).…”
Section: Discussionmentioning
confidence: 99%
“…They are seen in up to half of second-trimester fetuses and are often found with other anomalies. [3][4][5][6][7][8][9][10][11][12][13] In the nearly 2 decades since the initial report by Chudleigh et al, 1 a large volume of literature has been published regarding the sonographic detection of choroid plexus cysts in the second trimester. Despite this, a consensus of opinion has yet to be reached on the genetic significance and appropriate management when these cysts are detected as an isolated finding.…”
mentioning
confidence: 99%
“…Salihu et al 6 found that of their 11 cases of trisomy 18, only 64% had prenatally detected sonographic anomalies, with polyhydramnios (n = 4) being the most commonly seen abnormality. Bundy et al 3 found that of 12 cases with antenatal sonograms available, the actual diagnosis of trisomy 18 was suggested antenatally only twice, and chromosomal studies were prompted by sonographic findings in only 4 cases. In 1993, Nyberg et al 2 found that when choroid plexus cysts were excluded, 83% of fetuses with trisomy 18 (39 of 47) had 1 or more sonographic abnormalities (range, 0-6) identified.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] There are several studies that have described the types and frequencies of prenatal sonographic findings in fetuses with trisomy 18. [2][3][4][5][6] However, in most studies, descriptions of the normal content and detail of their routine prenatal sonographic examinations were not provided. Only 2 studies provided descriptions about the content of the sonographic examinations in detecting trisomy 18.…”
mentioning
confidence: 99%
“…About 95% die in utero, of liveborn infants, only 50% live to 2 months and only 5-10% will survive their first year of life 2,3) . Congenital heart disease is the major cause of death 1,4) .…”
Section: Discussionmentioning
confidence: 99%